THE PREVALENCE OF MUSCULOSKELETAL DISORDERS AMONG MADRASSA TEACHERS AND STUDENTS A CROSS SECTIONAL STUDY (International Journal of Physiotherapy, 2016)
Introduction: Musculoskeletal Disorders (MSD) are the disorders that have been developed due to disadvantageous work settings and work related issues. It may involve different regions of body like upper extremity, lower extremity, cervical, back regions etc. The onset of these problems need to be known where as it is a common belief that it is caused by overuse. Madrassa simply means the school does in the English language where students gathered to learn and acquire knowledge whether Muslim, non-Muslim, or secular. Usually teachers in madrassa adopted to sit in some positions in which musculoskeletal system is placed under load. The objective of the study is to determine “The Prevalence of Musculoskeletal Disorders among Madrassa Teachers.”Methods: It was a cross sectional study. 109 madrassa teachers participated in the study; the study was conducted in Karachi. Self-assessment questionnaire was use to collect data. Data was analyzed using SPSS version 20.Results: A total of 109 madrassa teachers taken part in this research study almost all participants were male. There were two types of madrassa teachers; one is full time teachers (73.4%) and part time (26.6%). (58.7%) madrassa teachers were suffering from discomfort during teaching and 41.3 didn’t feel any discomfort, coming to pain regions 37 said they had back pain (33.9%), 35 said they had shoulder pain (35%), 37 said they had knee pain (24.8%) and four said they had heel pain (3.7%).Conclusion: The result showed that the madrassa teachers have high prevalence of Musculoskeletal Disorders. This comprises different regions of body like shoulder, back, knee and heel. This leads to the conclusion that these teachers are not at all aware of the consequences of MSD nor they are aware of the causes of these disorders. Also this was found that the facilities provided to these teachers were not up to the mark. When it comes to the working environment the technology of ergonomics has proved a lot, in minimizing the development of MSD. There is a need to provide education on ergonomics for madrassa teachers.